Pengaruh Etos Kerja Dan Disiplin Kerja Terhadap Efektivitas Kinerja Organisasi Pada PT. POS Indonesia (Persero) Malang - Diah Rusminingsih (Politeknik Negeri Batam, 2012)
This study aimed to test by simultan on the ethos work and discipline work to organizational performance effectiveness at PT. Pos Indonesia (Persero) Malang, to test by parsial on the ethos work and discipline work to organizational performance effectiveness at PT. Pos Indonesia (Persero) Malang and to know variable is which most dominant have an effect on to organizational performance offectiveness at at PT. Pos (Persero) Malang. This research use approach of explanatory research. Dependent variable are X1 is ethos work and X2 is work discipline and independent variable (Y) is organizational performance effectiveness. Questionery, interview, and observation method used in this study with the number of respondents of 60 people. Double linear regression was used to analyze variables by using statistic program (SPSS). The result of research indicates that: a) by simultan, ethos work and work discipline have an effect on to organizational performance effectiveness at PT. Pos Indonesia (Persero) Malang. b). by partial, ethos work and work discipline have an effect on to organizational performance effectiveness at PT. Pos Indonesia (Persero) Malang c). Pursuant to coefficient value of regression among ethos work variable and work discipline, hence variable having dominant influence to organization performance effectiveness at PT. Pos Indonesia (Persero) Malang is work discipline, where its coefficient value equal to 0,400. This matter can be concluded that work discipline is variable having influence most dominant to organizational performance effectiveness at PT. Pos Indonesia (Persero) Malang.